Molecular Profiling Of Bauhinia Accessions Using Rapd Markers - DR. SHIJU MATHEW, (International Journal of Pharma and Bio Sciences, 2010)
The paper is a recent technology of the molecular study dealing with the molecular profiling of species. Here the elucidation of Bauhinia accession was done by using RAPD markers. The experiment was done in three steps: (i) Isolation and purification of genomic DNA from leaf tissues of Bauhinia, (ii) Generation of molecular profiles of Bauhinia using RAPD based DNA marker system and (iii) Evaluation of genetic relatedness of the Bauhinia samples under study employing classificatory analysis. To achieve these objectives Bauhinia leaf samples were collected from the AAI-DU campus and surrounding areas of Allahabad. These leaf samples were further processed to obtain DNA using CTAB method and SDS method. The isolated DNA samples were separated on agarose gel by electrophoresis and visualized under UV transilluminator. It was observed that the DNAs obtained from CTAB method was of good quality compared to the DNA isolated by the SDS method. Hence the DNA obtained from CTAB method was used for further PCR and RAPD analysis. The RAPD primer screening was done with 15 primers and out of which, the data of 9 primers were used for further analysis. From distance data, NJ tree was generated. The NJ tree indicates that the dendrogram was divided into two groups. The Bauhinia samples 8 and 9 were distant from rest of all the Bauhinias whereas the Bauhinia samples 11 and 12 were most similar to each other. The present study was done to provide foundation for advanced R&D methodologies such as that ones which employed in Biodiversity and Genetic diversity analysis.